2011
DOI: 10.1108/15265941111112820
|View full text |Cite
|
Sign up to set email alerts
|

Financial development index and economic growth: empirical evidence from India

Abstract: Purpose -The purpose of this paper is to construct a financial development index (FDI) for the Indian economy and also examine the relationship between FDI and economic growth. Design/methodology/approach -Augment Dickey Fuller, Phillips Perron and Ng Perron unit root tests are employed in order to determine the level of integration. The long-and short-run dynamics are obtained by using auto-regressive distributed lag approach to cointegration and rolling window approach to estimate coefficient of each observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Khan and Qayyum (2007) found a1 percent increase in RIR and FDI enhances economic growth by 0.03 and 1.029% respectively in Pakistan; and Kar et al (2008) found a 1% increase in FDI promotes economic growth by 0.015% for Turkey. Hye (2011) found 1% increase in RIR and financial indicator enhances economic growth in China by 0.015 and 0.25%, respectively (all interpretations are on an average and ceteris paribus). The present paper rejects the positive relationship between finance and economic growth in Bangladesh found earlier by Rahman (2004Rahman ( , 2007.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Khan and Qayyum (2007) found a1 percent increase in RIR and FDI enhances economic growth by 0.03 and 1.029% respectively in Pakistan; and Kar et al (2008) found a 1% increase in FDI promotes economic growth by 0.015% for Turkey. Hye (2011) found 1% increase in RIR and financial indicator enhances economic growth in China by 0.015 and 0.25%, respectively (all interpretations are on an average and ceteris paribus). The present paper rejects the positive relationship between finance and economic growth in Bangladesh found earlier by Rahman (2004Rahman ( , 2007.…”
Section: Resultsmentioning
confidence: 92%
“…This result is consistent with the findings of Hye (2011) for India but not with those found by Khan and Qayyum (2007) for Pakistan, and Hye and Dolgopolova (2011) for China. Hye's (2011) estimates suggest that a 1% increase in RIR lowers economic growth by 0.04% in India. Khan and Qayyum, and Hye and Dolgopolova found that a 1% increase in RIR enhances economic growth by 0.03% in Pakistan and 0.015% in China, on average ceteris paribus.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The large strand of the previous literature is focused on examining the correlation between FD and growth. The majority of this literature established a positive relationship (Adna Hye, 2011;Agbetsiafia, 2004;Atindehou et al, 2005;Beck & Levine, 2004;Campos et al, 2012;Ciftci et al, 2017;Herwatz & Walle, 2014;Jalil & Ma, 2008;Levine & Zervos, 1998;Pradhan, 2014;Pradhan et al, 2017;Zhang et al, 2012). In contrast, Hye and Islam (2013) and Narayan and Narayan (2013) found a negative relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, Acharya et al (2009) investigated the relationship between the financial development and economic growth in different sets of Indian states including BIMARU and nine other states using the credit outstanding as an indicator of financial development and confirmed the relationship between financial development and growth in Indian states. Hye (2011) identified the relationship between financial development and economic growth by constructing an index of financial development including four financial variables. The findings of the study suggested that during most of the years the index negatively related with economic growth of the country.…”
Section: Literature Reviewmentioning
confidence: 99%